2016
DOI: 10.1161/circinterventions.115.003288
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Routine Fractional Flow Reserve Evaluation During Coronary Angiography on Management Strategy and Clinical Outcome

Abstract: Background-Penetration of fractional flow reserve (FFR) in clinical practice varies extensively, and the applicability of results from randomized trials is understudied. We describe the extent to which the information gained from routine FFR affects patient management strategy and clinical outcome. Methods and Results-Nonselected patients undergoing coronary angiography, in which at least 1 lesion was interrogated by FFR, were prospectively enrolled in a multicenter registry. FFR-driven change in management st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 27 publications
(36 reference statements)
8
26
1
1
Order By: Relevance
“…Thus, the FFR guided treatment could have been more economical in daily practice if decision making for PCI relies more strictly on FFR value. 22 Baptista et al 23 demonstrated that routine assessment of coronary lesions by FFR, safely changes patient management strategy in half of the patients with a low likelihood of events in deferred revascularization. In addition, our present study is very much consistent with Baptista et al, where we deferred PCI in more than 50% of patient based on FFR value <0.75 and waiting to observe an events in future if any.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the FFR guided treatment could have been more economical in daily practice if decision making for PCI relies more strictly on FFR value. 22 Baptista et al 23 demonstrated that routine assessment of coronary lesions by FFR, safely changes patient management strategy in half of the patients with a low likelihood of events in deferred revascularization. In addition, our present study is very much consistent with Baptista et al, where we deferred PCI in more than 50% of patient based on FFR value <0.75 and waiting to observe an events in future if any.…”
Section: Discussionmentioning
confidence: 99%
“…Eine PCI sollte bei pathologischer FFR erfolgen und bei einer FFR ≥ 0,80 nicht durchgeführt werdendies gilt aufgrund der prognostischen Bedeutung auch für asymptomatische Patienten [1]. Dieses Vorgehen führt häufig zu einer Veränderung der Therapieregimes [25].…”
Section: Datenlage Zur Fraktionellen Flussreserveunclassified
“…The POST-IT (Portuguese Study on the Evaluation of FFR Guided Treatment of Coronary Disease) study 7 including ≈1000 patients and published in this issue of Circulation: Cardiovascular Interventions provides additional fuel to this emerging concept. Altogether, R3F, RIPCORD, and POST-IT are combining >2000 patients while sharing a similar prospective design to investigate the role of routine FFR at time of angiography on the therapeutic decision process.…”
Section: See Article By Baptista Et Almentioning
confidence: 99%
“…A key addition of the POST-IT study 7 is the demonstration that the implementation of routine FFR during angiography as the potential to reduce drastically the use of noninvasive tests. In this study, physicians requested the performance of a noninvasive test to clarify the patient management after coronary angiography in 22% of cases.…”
Section: See Article By Baptista Et Almentioning
confidence: 99%
See 1 more Smart Citation